Optimalisasi Manajemen Pendidikan untuk Peningkatan Mutu Lulusan Melalui Kebijakan Pendidikan Program Hasil Terbaik Cepat - Angelica Silfana (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to analyze the effectiveness of the implementation of the Fast Best Results Program education policy in improving the quality of graduates in educational institutions. The background of this study is based on the challenges faced by the world of education in the global era, such as curriculum mismatch, less innovative learning methods, and limited infrastructure that impact the low competitiveness of graduates. This study uses a qualitative approach with a case study method, conducted in schools that have implemented the program. Data collection techniques were carried out through in-depth interviews, observation, and documentation, with key informants consisting of principals, teachers, students, and parents. The results of the study indicate that the Fast Best Results Program is generally effective in encouraging improvements in learning management, increasing curriculum relevance, and increasing student competency. Supporting factors for the program's success include strong school leadership, ongoing teacher training, and parental support. The main obstacles include limited digital resources, teacher administrative burdens, and resistance to change. This study concludes that optimizing education management through focused and adaptive policies can significantly improve graduate quality. These findings are expected to provide strategic input for policymakers and education practitioners in designing contextual and sustainable quality improvement programs.